Microsituation Concept in GMES Decision Support Systems - Kuzemin, O.; Lyashenko, V. (Sofia: ITHEA, 2011)
A set of situation representation levels of subject domain naturally increases in emergency situations. This is connected with increased influence of subject domain factors on prototype system, independently of emergency conditions. So, for emergency situations of possible snow avalanches microsituations could differ of small differences of temperature or changes in wind speed. Development of financial crisis as emergency economic situation is characterized by separate characteristics of microsituations of different facilities, involved in economical process. Hence, situation includes a set of separate microsituations, each describing properties of prototype system in some characteristic category of its subject domain. Such categories for subject domain could represent internal and external processes, characteristics, advices both from prototype system’s point of view and set of factors which influence from subject domain to prototype system. Separate set of such characteristics without interconnections could hardly precisely describe a situation, because such characteristics are interconnected with each other, involved in different process of prototype system studying.
Keywords: microsituations; economical process; situational analysis; expert system